Complete and Durable Response to Combined Chemo/Radiation Therapy in EGFR Wild-Type Lung Adenocarcinoma with Diffuse Brain Metastases - Davide Adriano Santeufemia; Giuseppe Palmieri; Antonio Cossu; Valli De Re; Laura Caggiari; Mariangela De Zorzi; Milena Casula; Maria Cristina Sini; Giovanni Baldino; Maria Filomena Dedola; Giuseppe Corona; Gianmaria Miolo (Diagnostics, 2019)
Most non-small-cell lung cancer (NSCLC) patients are likely to develop brain metastases during the course of their illness. Currently, no consensus on NSCLC patients’ treatment with brain metastasis has been established. Although whole brain radiotherapy prolongs the median survival time of approximately 4 months, a cisplatin-pemetrexed combination may also represent a potential option in the treatment of asymptomatic NSCLC patients with brain metastases. Herein, we report the case of a non-smoker male patient with multiple, large and diffuse brain metastases from an “epidermal growth factor receptor (EGFR) wild-type„ lung adenocarcinoma who underwent an overly aggressive chemo/radiation therapy. This approach led to a complete and durable remission of the disease and to a long survival of up to 58 months from diagnosis of primary tumor. The uncommon course of this metastatic disease induced us to describe its oncological management and to investigate the molecular features of the tumor.